Sifat Fisikokimia dan Sensori Mie Basah dengan Substitusi Tepung Ubi Jalar Ungu - Desy Triastuti (Scientific Timeline, 2021)
Purple sweet potato is nutritional food containing high anthocyanin, fiber, and low glycemic index. Wet noodles in which substitution with purple sweet potato flour could be a healthy food choice. The physicochemical and sensory properties of wet noodles with purple sweet potato flour substitution were investigated. This study was conducted using a Completely Randomized Design (CRD) single factor with 3 substitution treatments for purple sweet potato flour to wheat flour (0%, 20%, and 40%). The parameters analyzed included physicochemical properties (moisture, ash, carbohydrates, protein, fat, and anthocyanin content) and sensory properties of wet noodles. Data analysis uses ANOVA, and it was followed by DMRT test if there was a significant difference (α = 0.05). The results showed that the substitution of sweet potato flour had a significant effect on the water, ash, protein, carbohydrate, and anthocyanin content. The highest anthocyanin levels were shown in the 40% treatment. Sensory test results showed that the proportion of purple sweet potato flour in wet noodles had a significant effect on texture, aroma, and preference for color, yet no significant effect on the taste preference. The substitution of up to 40% still produced good wet noodles and meet the quality requirement of SNI.